Bimetallic nickel-ferrite nanorod particles: greener synthesis using rosemary and its biomedical efficiency. Issue 1 (1st January 2020) - Alijani, Hajar Q.; Pourseyedi, Shahram; Torkzadeh-Mahani, Masoud; Seifalian, Alexander; Khatami, Mehrdad
Abstract: Nickel-ferrite (NiFe2 O4 ) nanorods particles (NRP) was biosynthesised for the first time by the Rosemary Extract. The NRP was fully characterised, including the type, nanostructure and physicochemical properties of using XRD, HRTEM, FeSEM, XPS, FTIR and VSM. TEM confirmed rod-shaped nano-sized particles with average sizes ranging from 10 nm to 28 nm. The EDAX Analysis showed the presence of iron, nickel, oxygen, and carbon. XRD analysis confirmed the synthesis of NiFe2 O4 crystals. XPS curves showed photoelectron for iron, oxygen and nickel. EDS showed the atomic, weight percentages ratios of Ni(12%): Fe(24%) and: O(48) are close to the theoretical value (Ni: Fe: O  = 1:2:4), of bimetallic magnetic NiFe2 O4 NRP. NiFe2 O4 NRP had cytotoxicity effect on MCF-7 cells survival which suggests that NiFe2 O4 NRP can be used as a new class of anticancer agent in design novel cancer therapy research. Graphical Abstract: UF0001